ANALISIS YURIDIS TERHADAP PRODUKSI BAJA TULANGAN BETON NON STANDARDISASI INDONESIA DITINJAU DARI UNDANG-UNDANG NOMOR 3 TAHUN 2014 TENTANG PERINDUSTRIAN (STUDI KASUS: PUTUSAN NOMOR 352/PID.SUS/2018/PN.PDG) - Renaldy Renaldy; Ariawan Gunandi (Jurnal Hukum Adigama, 2021)
In industrial law, concrete reinforcing steel is one of the products that are often found in daily practice for building construction foundations. Producers, distributors, and consumers have traded, transported and produced reinforcing steel which did not comply with Indonesian national standards. Besides this activity is very dangerous for the community and users, it can also hamper domestic growth in Indonesia. Therefore, there is a need for further research using several theories of corporate crime and civil theory to see how legal accountability is for perpetrators of law violators. However, the application of the theory of corporate crime still raises pros and cons due to different perceptions from experts. Thus, this research was conducted to find a common thread in order to achieve clarity of legal responsibility for the production of steel reinforced concrete in cases of violations of Indonesian national non-standard reinforced concrete steel.